Financial liberalization, financial development and productivity growth: An overview - Agnieszka Gehringer (Kiel Institute for the World Economy (IfW), 2013)
The paper surveys the literature on the effects of finance on productivity growth. In both the theoretical and empirical literature, there is no consensus regarding the contribution of financial liberalization and financial development to growth. Focusing on the direct channels of growth, the author has found both positive and negative contribution of finance to growth. Clearer positive effects emerge when considering growth channels related to productivity dynamics, with the estimated effects being positive and statistically distinguishable from zero.
Keywords: F32; F33; F36; 330; FDI; financial liberalization; financial development; productivity; growth; review